Perbedaan Kontrol Diri Ditinjau dari Pola Asuh Orang Tua pada Remaja di Desa Babelan Kota - Maryana, Dina; Kristiyani, Veronica (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, Sumatra Selatan, 2023)
Failure to carry out the process of emotional development in the adolescent phase properly causes a phenomenon of deviant behavior carried out by teenagers in Babelan Kota Village, teenagers who commit crimes have low self-control or self-control. Self-control in adolescents will cause adolescents to have no self-limitation against negative environmental influences, the formation of self-control by how parents provide parenting to adolescents. The purpose of this study was to see if there were differences in self-control in terms of parenting styles for adolescents in Babelan Kota Village. This research method uses a comparative causal quantitative method using a non-probability sampling technique with purposive sampling and the number of samples is 110 respondents. The data was collected using a self-control questionnaire and parenting styles, which were processed using the One Way Anova test statistic technique and the Post Hoc Test. The results of the hypothesis obtained the value of sig. 0.028 < 0.05, it is known that there is a significant difference between self-control in terms of parenting in adolescents in Babelan Kota Village, so this means that the hypothesis is accepted. Meanwhile, the results of the Post Hoc Test show that permissive parenting provides more opportunities in forming self-control for adolescents in Babelan Kota Village, with a mean difference of 3.819.